Iconoclasty as a demand for memory, space and time: a study on destruction of confederate monuments in the United States: um estudo da destruição dos monumentos confederados nos Estados Unidos - Marques dos Santos, Sandro (Revista Aedos, 2025)
For decades, the black movement in the United States has been calling for the removal of Confederate monuments in the country’s public spaces. Faced with the restrictions on this outcry, anti-racist protesters have appealed to the use of direct action in the destruction, graffiti or even popular removal of these monuments. Thus, my intention is to address how the existence and meaning of these monuments were disputed through these political acts of destruction. What are the consequences of these acts? What reasons led these monuments to be targeted? What claims were made by the protesters? What meaning does the dispute over these monuments have for the anti-racist struggle in the United States?